Faktor Risiko yang Mempengaruhi Hipertensi pada Perokok Usia Produktif di Indonesia : (Analisis Data Sekunder IFLS 2015) - Ni Ny. Wedarthani Achintya A; I Komang Peri Sukma Rahmawan; Tamina Melindah; Ega Delva; Diah Astini Paramitha (Journal of Educational Innovation and Public Health, 2026)
Smoking behavior is a modifiable risk factor for hypertension, with hypertension prevalence generally increasing alongside higher cigarette consumption and longer smoking duration. Research on hypertension prevalence among productive-age smokers in Indonesia using national-scale data remains scarce in Indonesian publications. This study aims to analyze factors influencing hypertension among productive-age smokers in Indonesia in 2015, utilizing data from the Indonesia Family Life Survey (IFLS) 2015. The research employs a quantitative design with an analytical observational approach using a cross-sectional study. The sample comprises 10,677 productive-age smokers in Indonesia, selected via multi-stage random sampling across 32 provinces in 2015. Independent variables include age, gender, employment status, work region, cigarettes smoked, smoking duration, and daily cigarette consumption, while the dependent variable is hypertension. Hypertension prevalence among productive-age smokers in Indonesia in 2015 reached 8.53%, with significant predictors including age ≥36 years, female gender, employment status, smoking intensity of 21–30 or >31 cigarettes/day, and smoking duration >16 years—reflecting multifactorial interactions of biological, behavioral, and socioeconomic factors. Accordingly, recommendations include routine screening at primary health centers for at-risk groups, tobacco control programs based on dose-duration, economic empowerment for the unemployed, intensive screening with lifestyle counseling by healthcare providers, and longitudinal designs for future causal studies.